1996
DOI: 10.1080/10430719608404853
|View full text |Cite
|
Sign up to set email alerts
|

What determines military allocations in Africa: Theoretical and empirical investigations

Abstract: This paper investigates theoretically and empirically the determinants of military spending in Africa. It specifies a formal model and uses time-series and cross-sectional estimations to ascertain the reasons behind variations in military allocations across and within 40 African countries during 1960-1991. The differences in military expenditures appear to reflect a complex of economic, political, and strategic factors at both national and international levels. Strategic considerations are, however, found to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…War has certainly accelerated the process of state collapse, and this has disproportionately affected the poor (Luckham 1999). A cross-national study by Mohammed (1996) found that increased military spending tends to go hand-inhand with reduced tax collection, or a decline in GDP, or both. In the 16 countries experiencing major conflicts during the 1970s and 1980s, Stewart et al (1997) found that, during their conflict periods, GDP per capita, food production per capita, the value of exports, the gross domestic savings ratio, and government expenditures as a percentage of GDP all declined; meanwhile, there was an increase in budget deficits and inflation rates.…”
Section: Ii1a Exposurementioning
confidence: 99%
“…War has certainly accelerated the process of state collapse, and this has disproportionately affected the poor (Luckham 1999). A cross-national study by Mohammed (1996) found that increased military spending tends to go hand-inhand with reduced tax collection, or a decline in GDP, or both. In the 16 countries experiencing major conflicts during the 1970s and 1980s, Stewart et al (1997) found that, during their conflict periods, GDP per capita, food production per capita, the value of exports, the gross domestic savings ratio, and government expenditures as a percentage of GDP all declined; meanwhile, there was an increase in budget deficits and inflation rates.…”
Section: Ii1a Exposurementioning
confidence: 99%